Determinant of Primary Preventive Behaviour Cervical Cancer in an Adolescent Girl - Dwi Helynarti Syurandhari; Deni Susyanti; Irma Handayani; Fitriani Pramita Gurning; Muchti Yuda Pratama; Muh Zul Azhri Rustam (Institute of Medico-legal Publications Pvt Ltd, 2021)
Cervical cancer is caused by infection with the human papilloma virus which can infect the genitals, anus,throat, mouth and cells on the surface of the skin. Cervical cancer is often late so that it can cause death,so efforts are needed to reduce the risk factors for cervical cancer, namely through primary preventionefforts. The purpose of this study was to determine the relationship between primary factors and cervicalcancer prevention behavior in adolescent girls. The sample in this study were 77 young women who weretaken by technique purposive sampling. The research design used was an observational analysis using across sectional approach and analyzed using chi-square. The results of this study illustrate that there is arelationship between knowledge, attitudes and social support with cervical cancer prevention behavior inadolescent girls. So we need efforts to reduce cervical cancer risk factors, namely through primary preventionefforts, by increasing outreach activities in the community to carry out a healthy lifestyle.